Social Sustainability in the Management Zones of Mounts Timpoong-Hibok Hibok Natural Monument, Philippines - Morados, Alexander N. (Nusantara Science and Technology Proceedings, 2025)
Social sustainability is an interdisciplinary approach that ensures human needs are attainable by all and resources are available to all in the community. The study aims to assess the sustainability of social aspects in the multiple-use zone and the buffer zone of Mts Timpoong-Hibok Hibok Natural Monument, Camiguin, Philippines to serve as the basis for sustainable management of the area. The main methods used are descriptive surveys, focus group discussions, and key informant interviews. It also utilized the Basic Social Sustainability Assessment System using 5 criteria and 9 indicators with the Sustainability Index from 0 (lowest level) to 1 (highest level). Among the criteria considered for social sustainability in the upland farming communities, the infrastructure of 0.88 is considered sustainable; Access to basic services reached 0.71 and Population 0.81 at a fairly sustainable level, economic criteria reached 0.411 at an average sustainable level, the lowest was the criterion on educational conditions at 0.273 at a less sustainable level. Based on the analysis of social sustainability factors, a comprehensive, and participatory development plan should be put into place by all stakeholders.